The Effectiveness of The Marriage Management Information System (SIMKAH) Program as an Effort to Prevent Data Manipulation - Bambang Hardiyanto Laga; Aplonia Pala; Anita Lassa (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2022)
The problem in this study is that there are some Muslims who are trying to manipulate marriage data because they want to perform a nationwide legal double marriage. With this problem that occurs almost in all parts of Indonesia, the Director General of Bimas Islam issued the instruction number DJ.II/369 of 2013 on the implementation of the Marriage Management Information System (SIMKAH) in the Office of Religious Affairs (KUA) sub-district The problem in this study is that there are some Muslims who try to manipulate marriage data because they want to perform a nationwide legal double marriage. However, when using the SIMKAH application, there are also recurring server errors caused by dense access to the central SIMKAH server. The purpose of this study is to describe the effectiveness of the Marriage Management Information System Program (SIMKAH) to prevent data manipulation in the Religious Affairs Office (KUA) of Kefamenanu City District, TTU Regency. This research is a descriptive research with a qualitative approach, so the technical data analysis is presented in the form of a presentation or overview of the findings in the field, both in the form of data and information from interviews and other documents. The results of the research in the field show that since the use of SIMKAH application, KUA Kefamenanu Municipality recorded as many as 18 data manipulation experiments conducted in 2018-2020. This SIMKAH application is very effective in the effort to prevent manipulation of marriage data, because the SIMKAH application has been linked to the data of DUKCAPIL, so that only by entering the NIK of the bride and groom, all the data will appear automatically, starting from name, birthplace, date, address, parents' name and marital status. Future brides whose dates are married will need to provide a divorce certificate to register a second marriage, which will be uploaded to the SIMKAH application. If the person cannot provide the divorce certificate, the marriage registration process will not proceed.